Experimental and quantum chemical studies on SHG, Z-scan and optical limiting investigation of 2-amino-5-bromopyridinium trifluoroacetate single crystal for optoelectronic applications. (January 2020) - Saravanakumar, M.; Chandrasekaran, J.; Krishnakumar, M.; Babu, B.; Vinitha, G.; Anis, Mohd
Abstract: The 2-amino-5-bromopyridinium trifluoroacetate (2A5BPTFA) crystal has been successfully grown by solvent slow evaporation technique. The grown crystal is found to non-centrosymmetric space group Pna21 with orthorhombic crystal system, which has been confirmed from single crystal X-ray diffraction analysis. The crystalline nature of the 2A5BPTFA is supported by powder X-ray diffraction technique. The molecular structure and different functional groups in 2A5BPTFA were confirmed by 1 H, 13 C NMR and FTIR spectral analyses. The intermolecular charge transfer that occurs in 2A5BPTFA molecule due to the presence of N–H⋯O and C–H⋯O hydrogen bondings have been studied by Hirshfeld surface analysis. From the UV–Vis absorption and photoluminescence spectra, the lower cutoff wavelength and emission peak are found to be 364 nm and 392 nm, respectively. In addition, the optical band gap of grown crystal has been calculated as 3.47 eV. Powder second harmonic generation efficiency of the crystal is observed to be 2.44 times greater than that of potassium dihydrogen phosphate. A positive photoconducting nature and low dielectric constant values have been obtained from photoconductivity and dielectric studies. From the Z-scan study reveals the self-defocusing nature of the grown crystal. Optical limiting study shows the optical limiting response of 2A5BPTFA crystal. In addition, the intermolecular charge transfer interactions and existence of N–H⋯O hydrogen bonding of the 2A5BPTFA have been confirmed by density functional theory methods and are discussed in detail. Highlights: The research discloses the discovery of novel 2-amino 5- bromopyridinium trifluoroacetate (2A5BPTFA) as an efficient organic material for NLO applications. 2A5BPTFA exhibits blue emission confirmed by Photoluminescence studies, which proves to be an eligible candidate of fabrication of blue organic-LED. This is exhibits second harmonic generation. The relative NLO efficiency of 2A5BPTFA has 2.44 times larger than that of KDP. The study report 2A5BPTFA exhibits self-focusing nature and the optical limiting threshold values confirm the suitability in optoelectronic applications.